REAKSI ESTERIFIKASI GARAM ASAM LEMAK DENGAN ALKIL KLORIDA BERANTAI PANJANG MENGGUNAKAN TRIDODEKILAMIN HIDROKLORIDA SEBAGAI KATALIS PERPINDAHAN DUA FASA - Aritonang, Henry F.; Tangkuman, Herling D. (CHEMISTRY PROGRESS, 2009)
Synthesis of didodekyl azelate produced by estherification reaction of disodium azelate salt with dodecylchloride used tridodecylamine hydrochloride as catalyst of two phase transfer was 34,123 gram (65,11%). Product of ester didodekyl azelate was identified by IR spectrometry which shows strong absorptionat 1700-1600 cm-1 indicating ester group C=O and 1H-NMR spectra showed that the number of protonsester was five lingkungan chemistry yang berbeda.